2020
DOI: 10.1090/proc/14925
|View full text |Cite
|
Sign up to set email alerts
|

The convergence of discrete Fourier-Jacobi series

Abstract: The discrete counterpart of the problem related to the convergence of the Fourier-Jacobi series is studied. To this end, given a sequence, we construct the analogue of the partial sum operator related to Jacobi polynomials and characterize its convergence in the ℓ p (N)-norm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The result for the convergence of the Fourier-Jacobi series of f on the entire segment of orthogonality [−1, 1] established by Belen'kii [2] in 1989 is stated below. 3 Random Fourier-Jacobi series associated with symmetric stable process Let X(t, ω) be a symmetric stable process of index α ∈ [1,2]. Consider the random Fourier-Jacobi series…”
Section: Definition 21 ([4]mentioning
confidence: 99%
See 3 more Smart Citations
“…The result for the convergence of the Fourier-Jacobi series of f on the entire segment of orthogonality [−1, 1] established by Belen'kii [2] in 1989 is stated below. 3 Random Fourier-Jacobi series associated with symmetric stable process Let X(t, ω) be a symmetric stable process of index α ∈ [1,2]. Consider the random Fourier-Jacobi series…”
Section: Definition 21 ([4]mentioning
confidence: 99%
“…It is observed that the sum function of the random Fourier-Jacobi series (9) associated with symmetric stable processes X(t, ω) of index α ∈ [1,2] is weakly continuous in probability, where as the sum function of the random series (24) associated with Wiener process is continuous in quadratic mean. It is known that a function f (t, ω) is said to be weakly continuous in probability at t = t 0 , if for all > 0, lim h→0 P (|f (t 0 +h, ω)−f (t 0 , ω)| > ) = 0.…”
Section: Continuity Property Of the Sum Functionsmentioning
confidence: 99%
See 2 more Smart Citations